Investigating the Effects of Active Cooling in 3D Printing - Ficzere, Péter (International Journal of Engineering and Management Sciences, 2022)
3D printing is an increasingly widespread manufacturing process. With the development of machines and materials, the technology is becoming more accessible and easier to use. However, the technology's specificities mean that it requires knowledge of manufacturing technology. In some cases, it is necessary to solidify the freshly deposited layers as soon as possible in the event of large overhangs. This can be achieved by active cooling, which in turn can affect the material properties of the part. This research investigates the effects of active cooling during production.